The Role of Trust In Mediating Personal Selling and Customer Experience Towards The Decision To Save at BPR Syariah: Study at BPRS Baiturridha Pusaka-Bandung - Hindun, Kiftiah; Anwar, Muhadjir; Purwanto, Sugeng (Economics and Business Journal (ECBIS), 2025)
This research is motivated by the importance of building customer trust inencourage customer interest and decisions to save regularly at BPR Syariah, especially through strengthening personal selling marketing communication strategies and positive service experiences. The main theory underlying this research is the Theory of Planned Behavior (TPB). This research aims to analyze (1) the influence of personal selling on saving decisions, (2) the influence of customer experience on saving decisions, (3) to determine whether trust mediates the relationship between personal selling and saving decisions, (4) to determine whether trust mediates the relationship between customer experience and saving decisions at BPRS Baiturridha Pusaka-Bandung. This study uses a quantitative approach through the Structural Equation Modeling–Partial Least Squares (SEM–PLS) method. The sample consisted of 120 active customer respondents of BPRS Baiturridha Pusaka-Bandung selected using a probability sampling technique through a simple random sampling approach, where each member of the population has an equal chance of being selected as a respondent. Data collection was carried out through the distribution of structured questionnaires and analyzed using Smart PLS software version 3.0. The results of the study show that (1) Personal Selling does not influence the decision to save (2) Customer Experience has a positive and significant influence on the Decision to Save (3) Trust is not proven to significantly mediate the relationship between personal selling and the decision to save (4) Trust is proven to significantly mediate the relationship between customer experience and the decision to save. These findings confirm that in the context of BPR Syariah, positive customer experience is the main factor in forming trust and driving savings behavior